Enhancing biochar steam gasification via frequency-tuned microwave heating for efficient CO2-to-CO conversion - Xinru La; Haolin Liu; Wei Liao; Xi Lin; Bingqing Shi; Yunjuan Sun; Jurong Ren; Lingming Xiong; Shule Wang; Jia Wang; Jianchun Jiang (Biomass and Bioenergy, 2026)

Unlocking the potential of urban spatial structure to shape building energy demand at a large scale - Haolin Wang; Zhi Wu; Wei Gu; Pengxiang Liu; Qirun Sun; Wei Wang (Sustainable Cities and Society, 2026)

Towards climate-resilient cities: assessing and planning urban energy demand under extreme climate events - Haolin Wang; Zhi Wu; Wei Gu; Pengxiang Liu; Qirun Sun; Wei Wang (Energy and Buildings, 2026)

Integrating the Indexes of Energy and Food Security into the Measurement of Water-Energy-Food Nexus Efficiency Towards SDGs - Lina Zhang; Chenyu Sun; Liyin Zhang; Yung-ho Chiu; Haolin Yang; Qinghua Pang; Zhen Shi (Water Resources Management, 2026)

Microbial metabolism decline in degraded grasslands depends on soil organism size - Yang Hu; Mengfei Cong; Tianle Kou; Han Yan; Xinya Sun; Haolin Zhang; Yakov Kuzyakov; Yang Yang; Yimei Huang; Yanxing Dou; Zhaolong Zhu; Baorong Wang; et al. (Agriculture, Ecosystems & Environment, 2026)

Increased Contributions of Microbial Extracellular Polymeric Substance to Soil Organic Carbon During Grassland Degradation - Haolin Zhang; Ji Chen; Yang Hu; Xiaoxiang Sun; Jiacong Zhou; Yubin Wang; Bicheng Zhang; Kyungjin Min; Sergey Blagodatsky; Shaoshan An; Zhaolong Zhu (Global Change Biology, 2026)
Microbial residues are fundamental to the long‐term stabilization of soil organic carbon (SOC). Intensively used alpine grasslands are subject to degradation under climate change, which may profoundly reshape microbial life‐history strategies and SOC accumulation. However, the mechanisms by which grassland degradation influences the accumulation of different microbial residues and by which microbial life‐history strategies regulate these processes remain unclear. Addressing this research gap, we quantified microbial necromass carbon (MNC) and extracellular polymeric substance carbon (EPSC) and assessed their contributions to SOC in grasslands under different stages of degradation. We also investigated the impact of microbial growth and resource acquisition strategies on the accumulation of MNC and EPSC. We found that microbial residues were differentially influenced by grassland degradation. On average across the lightly, moderately, and heavily degraded grasslands, MNC declined by 69% relative to the non‐degraded grassland, whereas EPSC declined by only 15%. Interestingly, grassland degradation increased the ratio of EPSC to microbial biomass carbon by 1.4‐fold and its contribution to SOC by 1.2‐fold. The higher ratio of EPSC to microbial biomass carbon is indicative of rapid microbial biomass turnover, which in turn promotes EPSC's contribution to SOC. Enhanced EPSC accumulation under degradation was associated with shifts in microbial life‐history strategies, such as reduced carbon use efficiency, elevated metabolic quotient, and increased production of carbon‐acquisition enzymes. In contrast, there were no significant differences in the ratio of MNC to microbial biomass carbon or its contribution to SOC under the varying degradation intensity. In conclusion, this study provides novel and direct empirical evidence that EPSC plays an important role in SOC accumulation in degraded grasslands.

Combination of sludge free nitrous acid treatment in the presence of ammonium with intermittent aeration for rapid control of nitrate production in mainstream partial nitritation/anammox processes - Lei Liu; Jing Wu; Haolin Sun; Chao Wang; Yandong Yang; Weihua Zhao; Changqing Liu; Yong Tian (Journal of Environmental Chemical Engineering, 2025)

A GIS-Informed deep learning framework to assess the effect of urban morphology on energy demand - Haolin Wang; Zhi Wu; Wei Gu; Pengxiang Liu; Qirun Sun; Wei Wang (Energy and Buildings, 2025)

Decreased nematode energy flow triggers soil microbial necromass loss in degraded grasslands - Yang Hu; Mengfei Cong; Tianle Kou; Han Yan; Yuanbin Jia; Xinya Sun; Haolin Zhang; Bicheng Zhang; Yubin Wang; Hongtao Jia; Shaoshan An (Applied Soil Ecology, 2025)

Comparison of different operational modes for mainstream anammox process with multiple nitrite supply pathways: Significance of influent C/N ratio - Yanzhen Ren; Chao Wang; Jing Wu; Haolin Sun; Lei Liu; Yandong Yang; Changqing Liu; Yong Tian (Journal of Water Process Engineering, 2025)

Linking soil organic carbon mineralization to microbial interactions during alpine grassland degradation - Yang Hu; Xinya Sun; Haolin Zhang; Bicheng Zhang; Yubin Wang; Hongtao Jia; Chao Liang; Shaoshan An (Journal of Environmental Management, 2025)

Assessing water-energy-food nexus efficiency for food security planning in China - Lina Zhang; Haolin Yang; Yixin Chen; Yung-ho Chiu; Qinghua Pang; Chenyu Sun; Zhen Shi (Food Policy, 2025)

Glomalin-related soil proteins in particulate and mineral-associated organic carbon pools in alpine grasslands with different degradation degrees - Haolin Zhang; Yang Hu; Xinya Sun; Yubin Wang; Bicheng Zhang; Chunhui Liu; Anum Rafiq; Baorong Wang; Shaoshan An; Zhaolong Zhu (Applied Soil Ecology, 2025)

RTDETR-MARD: A Multi-Scale Adaptive Real-Time Framework for Floating Waste Detection in Aquatic Environments - Baoshan Sun; Haolin Tang; Liqing Gao; Kaiyu Bi; Jiabao Wen (Journal of Marine Science and Engineering, 2025)
Accurate and efficient detection of floating waste is crucial for environmental protection and aquatic ecosystem preservation, yet remains challenging due to environmental interference and the prevalence of small targets. To address these limitations, we propose a Multi-scale Adaptive Real-time Detector (RTDETR-MARD) based on RT-DETR that introduces three key innovations for improved floating waste detection using unmanned surface vessels (USVs). First, our hierarchical multi-scale feature integration leverages the gather-and-distribute mechanism to enhance feature aggregation and cross-layer interaction. Second, we develop an advanced feature fusion module incorporating feature alignment, Information Fusion, information injection, and Scale Sequence Feature Fusion components to ensure precise spatial alignment and semantic consistency. Third, we implement the Wise-IoU loss function to optimize localization accuracy through high-quality anchor supervision. Extensive experiments demonstrate the framework’s effectiveness, achieving state-of-the-art performance of 86.6% mAP50 at 96.8 FPS on the FloW dataset and 49.2% mAP50 at 107.5 FPS on our custom water surface waste dataset. These results confirm RTDETR-MARD’s superior accuracy, real-time capability, and robustness across diverse environmental conditions, making it particularly suitable for practical deployment in ecological monitoring systems where both speed and precision are critical requirements.

Selective G6PDH inactivation for Helicobacter pylori eradication with transformed polysulfide - Xiaonan Wang; Ning Zhou; Xuejiao J. Gao; Zijing Zhu; Minmin Sun; Qian Wang; Haolin Cao; Xuetong Wu; Caiyu Zhou; Qingkang Zheng; Ye Yuan; Yuan Liu; et al. (Science China Life Sciences, 2025)

Design, synthesis and systemic acquired resistance of 2-benzothiadiazolylquinoline-4-carboxamides by COI1 based virtual screening - Xiaoyu Liu; Hongwei Yang; Yaru Sun; Yuting Huang; Shuang Hong; Haolin Yuan; Wei Gao; Liangfu Tang; Zhijin Fan (Molecular Diversity, 2025)

Identification of Key Genes Correlated with Economic Trait Superiorities and Their SNP Screening Through Transcriptome Comparisons, WGCNA and Pearson Correlation Coefficient in the Sea Cucumber Apostichopus Japonicus - Jingxian Sun; Haolin Wang; Yaoyao Zhan; Tanjun Zhao; Chengda Li; Cao Cheng; Zengdong Wang; Ange Zou; Yaqing Chang (Marine Biotechnology, 2025)

2-Ethylhexyl diphenyl phosphate induces lung oxidative stress and pyroptosis in chicks - Yiming Sun; Ruili Zhang; Jiali Li; Yihan Hu; Haolin Zhang; Xiangjie Wang; Yi Yang; Haibin Wang; Ming Ge (Science of The Total Environment, 2025)

Exploring the impact of fulvic acid on electrochemical hydrogen-driven autotrophic denitrification system: Performance, microbial characteristics and mechanism - Haolin Chen; Meiyi Tang; Liang He; Xinxin Xiao; Fei Yang; Qiulai He; Shiquan Sun; Yang Gao; Lean Zhou; Yifu Li; Julong Sun; Wei Zhang (Bioresource Technology, 2024)

Key factors influencing wheat grain zinc and manganese concentration in areas with different soil available phosphorus - Chenrui Liu; Haolin Wang; Yue Ma; Peiyi Guan; Qing Sun; Ziming Wang; Zilin Wang; Zhaohui Wang; Mei Shi (Field Crops Research, 2024)

Adsorption-desorption of copper(II) by temperature-sensitive nano-biochar@PNIPAM/alginate double-network composite hydrogel: Enhanced mechanisms and application potentials - Haolin Chen; Yiwei Pan; Wei Zhang; Anlin Long; Mengqi Chen; Xinxin Xiao; Ziyi Wang; Meiyi Tang; Yazhou Peng; Shiquan Sun; Huining Zhang; Qiulai He (Chemical Engineering Journal, 2024)

A multifunctional nanoplatform for dual-readout visual detection and real-time inactivation of Staphylococcus aureus with nanozymes and Au nanorods - Ruimeng Sun; Hainan Ma; Han Wang; Yurou Wang; Lina Zhang; Xiaoyu Zhang; Haolin Sun; Haoran Zheng; Jiayu Guo; Na Guo; Yanfei Qi (Food Bioscience, 2024)

MEIAT-CMAQ: A modular emission inventory allocation tool for Community Multiscale Air Quality Model - Haofan Wang; Jiaxin Qiu; Yiming Liu; Qi Fan; Xiao Lu; Yang Zhang; Kai Wu; Ao Shen; Yifei Xu; Yinbao Jin; Yuqi Zhu; Jiayin Sun; et al. (Atmospheric Environment, 2024)

A programmable sensitive platform for pathogen detection based on CRISPR/Cas12a -hybridization chain reaction-poly T-Cu - Haolin Sun; Xiaoyu Zhang; Hainan Ma; Lina Zhang; Yang Zhang; Ruimeng Sun; Haoran Zheng; Han Wang; Jiayu Guo; Yanqi Liu; Yurou wang; Yanfei Qi (Analytica Chimica Acta, 2024)

Upcycling retired Li-ion batteries into high-performance oxygen reduction reaction electrocatalysts in flexible Al-air batteries - Haolin Hu; Yuelin Wang; Yue Xu; Liangxiao Jin; Samuel Jeong; Xinfu Xie; Chengqian Xiong; Bojun Zhou; Wenping Sun; Jialiang Zhang; Xi Lin; Kailong Hu (Chemical Engineering Journal, 2024)

Simultaneous modification of emission spectrum and trap distribution for achieving self-trapped excitons-based white afterglow - Huanxin Yang; Xiangxiang Chen; Haolin Lu; Wenda Sun; Yue Li; Yuhai Zhang; Yanjie Liang; Guankui Long; Libing Zhang; Xiyan Li (Chemical Engineering Journal, 2024)

Impact of grassland degradation on soil multifunctionality: Linking to protozoan network complexity and stability - Yang Hu; Haolin Zhang; Xinya Sun; Bicheng Zhang; Yubin Wang; Anum Rafiq; Hongtao Jia; Chao Liang; Shaoshan An (Science of The Total Environment, 2024)

Integrated metabolome–metagenome analysis provides new insights into the impacts of sea cucumber (Apostichopus japonicus) aestivation on marine sediment composition - Wenhong Mai; Jingxian Sun; Haolin Wang; Chengda Li; Zengdong Wang; Cao Cheng; Ange Zou; Yaoyao Zhan; Yaqing Chang (Aquaculture, 2024)

Comparative transcriptome analysis provides insights into the resistance regulation mechanism and inhibitory effect of fungicide phenamacril in Fusarium asiaticum - Zhitian Zheng; Huaqi Liu; Xiao Luo; Runze Liu; Alexander Dumbi Joe; Haolin Li; Haiyan Sun; Yanling Lin; Yanzhong Li; Yunpeng Wang (Pesticide Biochemistry and Physiology, 2024)

Insight into seismotectonics of the central-south Tanlu Fault in East China from P-wave tomography - Yejun Sun; Haibo Wang; Yun Huang; Junfei Wang; Haolin Jiang; Yicheng He; Zhouchuan Huang (Journal of Asian Earth Sciences, 2023)

Creation of robust oxygen vacancies in 2D ultrathin BiOBr nanosheets by irradiation through photocatalytic memory effect for enhanced CO2 reduction - Lizhen Lu; Haoyu Zhang; Zhe Sun; Jinghui Wang; Haolin Wang; Jinbo Xue; Qianqian Shen; Qi Li (Chemical Engineering Journal, 2023)

Protective effects of maternal administration of total saponins of Codonopsis pilosula in the mice offspring following diarrhea: role of immune function, antioxidant function, and intestinal inflammatory injury - Jiali Li; Yiming Sun; Naixi Yang; Haolin Zhang; Yihan Hu; Haibin Wang; Ruili Zhang; Ming Ge (Environmental Science and Pollution Research, 2023)

Research on a new-designed Venturi ejector and dazomet particle motion characteristics for dilute-phase pneumatic conveying systems based on CFD-DEM - Haolin Ma; Chunjiang Zhao; Shuo Yang; Si Li; Xiaohe Sun; Changyuan Zhai (Computers and Electronics in Agriculture, 2023)

Distribution and Controlling Factors of Dissolved Gaseous Mercury and Reactive Mercury in Seawater Near Yangtze River Estuary - Pingping Yin; Wen Zheng; Yan Wang; Ruhai Liu; Xin He; Haolin Sun; Dou Li (Journal of Ocean University of China, 2023)

Ecological carrying capacity and carbon sequestration potential of bivalve shellfish in marine ranching: A case study in Bohai Bay, China - Zepeng Li; Yan Chen; Gang Wang; Jiandong Mu; Yanfeng Sun; Haolin Yu; Jiangling Xu; Ying Yan; Shuangyue Luo; Fuqiang Han; Jie Feng; Zhe Pan (Frontiers in Marine Science, 2023)
Introduction Shellfish play an important role in ecological restoration and as carbon (C) sinks, but studies on their ecological carrying capacity (ECC) and C sequestration potential are sparse. Methods In this study, we selected a 57-hectare artificial oyster reef in a typical marine ranching in Bohai Bay, China, to evaluate the ECC and their C sequestration potential of bivalve shellfish, and projecting their impact on functional groups in the system, with an Ecopath with Ecosim (EwE) food web model. We conducted four biological surveys to obtain the biomass measurements, with one conducted in each of the summer, autumn, and winter of 2019 and one in the spring of 2020; and the functional groups included in the surveys comprised fish, cephalopods, crustaceans, snails, bivalve shellfish, annelids, other macrobenthos, meiobenthos, starfish, sea cucumbers, zooplankton, phytoplankton, and detritus. Results and Discussion The EwE model prediction results showed that the ECC of bivalve shellfish was established to be 282.66 t/km 2 , far more than the existing quantity of 187.76 t/km 2 . Therefore, at present, the ecosystem of the study marine ranching is not yet mature. Moreover, our ecological network analysis parameters indicated that the marine ranching ecosystem will be mature and stable when the bivalve shellfish population reaches its ECC. However, the increase in bivalve shellfish biomass will result in a decrease in the population sizes of species competing for food resources with bivalve shellfish, mainly gobiid fish such as Tridentiger bifasciatus, Tridentiger trigonocephalus, Tridentiger barbatus . Simultaneously, when the bivalve shellfish reach their ECC, 29.23 t of CO 2 can be sequestrated by bivalve shellfish, comprising 14.32 t being removed from the ecosystem as prey and 14.91 t being stored on the seafloor through biodeposition. Conclusion Therefore, the research demonstrated that, within the scope of ECC, the increasing bivalve shellfish can improve the C sequestration capacity of the marine ranch ecosystem, and effective management of bivalve shellfish in marine ranching can improve the economic benefits and C sink service functions of marine ranching.

Simple and sensitive electrochemical detection of sunset yellow and Sudan I in food based on AuNPs/Zr-MOF-Graphene - Ruimeng Sun; Ruijuan Lv; Yuhan Li; Ting Du; Lixia Chen; Yang Zhang; Xiaoyu Zhang; Lina Zhang; Hainan Ma; Haolin Sun; Yanfei Qi (Food Control, 2023)

Speciation and source changes of atmospheric arsenic in Qingdao from 2016 to 2020 - Response to control policies in China - Haolin Sun; Yan Wang; Ruhai Liu; Pingping Yin; Dou Li; Long Shao (Chemosphere, 2023)